2007
DOI: 10.1002/hbm.20417
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between motivational stance, cortical excitability, and the frontal electroencephalogram asymmetry of emotion: A transcranial magnetic stimulation study

Abstract: Several electrophysiological studies have provided evidence for the frontal asymmetry of emotion. In this model the motivation to approach is lateralized to the left, whereas the motivation to avoidance is lateralized to the right hemisphere. The aim of the present experiment was to seek evidence for this model by relating electrophysiological and phenomenological indices of frontal asymmetry to a direct measure of cortical excitability. Frontal asymmetrical resting states of the electroencephalogram and motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 47 publications
4
54
0
Order By: Relevance
“…It is suggested that beta power reflects inhibitory characteristics [14], thus, this finding suggests dominance of the right hemisphere over the left one when sensation of reality is low, due to left hemispheric inhibitory activity. Thus, withdrawal-related processes may occur during low sensation of reality, since this result is consistent with other studies that revealed left frontal beta activation [10,32] or right frontal increase in alpha EEG power [3] during withdrawal-related tasks. This indicates that sensation of reality is related to approach/withdrawal-related emotional processes, in the sense that low sensation of reality may lead to withdrawal-related emotional processes, whereas high sensation of reality to approach-related ones.…”
Section: Spatial Filterssupporting
confidence: 91%
“…It is suggested that beta power reflects inhibitory characteristics [14], thus, this finding suggests dominance of the right hemisphere over the left one when sensation of reality is low, due to left hemispheric inhibitory activity. Thus, withdrawal-related processes may occur during low sensation of reality, since this result is consistent with other studies that revealed left frontal beta activation [10,32] or right frontal increase in alpha EEG power [3] during withdrawal-related tasks. This indicates that sensation of reality is related to approach/withdrawal-related emotional processes, in the sense that low sensation of reality may lead to withdrawal-related emotional processes, whereas high sensation of reality to approach-related ones.…”
Section: Spatial Filterssupporting
confidence: 91%
“…While specific contributions to cognition and behaviour of the left and right DLPFC have been identified, 17,35-37 much less is known about the connectivity between these regions that presumably underlie cognition and behaviour. Some evidence suggests that connectivity between homotopical prefrontal regions may be implicated in approach versus withdrawal behaviour 38,39 in which psychopathic offenders may have subtle deficits. 40 Approach-related behaviour (i.e., behaviour directed at the attainment of rewards) recruits the left prefrontal cortex, whereas withdrawal-related behaviour (i.e., behaviour intended to avoid potential punishment) is associated with the right prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective trials in seniors will be conducted to explore early warnings for falls that can then be integrated in a system for fall prevention. Decrease of gait speed is of particular interest since it is a predictor for health-related events such as falls [5]. Introduction Despite a number of review article summarize the positive effect of physical exercise on the blood lipid profile, sometimes both literature and clinical practice report the inefficacy of physical exercise to improve plasma lipoprotein levels.…”
Section: Resultsmentioning
confidence: 99%
“…The equation (right-left)/(right+left) served to calculate frontal asymmetry as a marker of approach-related emotions [5].…”
Section: Methodsmentioning
confidence: 99%